2021
DOI: 10.3390/antiox10040526
|View full text |Cite
|
Sign up to set email alerts
|

Redox Homeostasis in Pancreatic β-Cells: From Development to Failure

Abstract: Redox status is a key determinant in the fate of β-cell. These cells are not primarily detoxifying and thus do not possess extensive antioxidant defense machinery. However, they show a wide range of redox regulating proteins, such as peroxiredoxins, thioredoxins or thioredoxin reductases, etc., being functionally compartmentalized within the cells. They keep fragile redox homeostasis and serve as messengers and amplifiers of redox signaling. β-cells require proper redox signaling already in cell ontogenesis du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 243 publications
(317 reference statements)
0
24
0
Order By: Relevance
“…On the other hand, β-cells have a lower abundance of antioxidant defense enzymes, such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx) [ 124 , 125 , 126 ]. As such, the administration of antioxidant supplements can increase the defense capacity of islet cells to cope with oxidative stress [ 127 ].…”
Section: Role Of Cd36 In Pancreatic β-Cell Pathophysiologymentioning
confidence: 99%
“…On the other hand, β-cells have a lower abundance of antioxidant defense enzymes, such as superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx) [ 124 , 125 , 126 ]. As such, the administration of antioxidant supplements can increase the defense capacity of islet cells to cope with oxidative stress [ 127 ].…”
Section: Role Of Cd36 In Pancreatic β-Cell Pathophysiologymentioning
confidence: 99%
“…Refs. (5,17,107,248)]. Type 2 diabetes etiology originates not only from the impaired molecular mechanisms of insulin secretion but also from low-grade inflammation causing insulin resistance and promoting b-cell oxidative stress, ER stress, and cell death.…”
Section: Basic Mitochondrial Contribution To Insulin Secretionmentioning
confidence: 99%
“…We found that insulin secretion stimulated by branchedchain ketoacids (BCKAs) (194) and partly by fatty acids (FAs) (98,103) essentially relies on mitochondrial retrograde redox signaling. Due to the relatively low content of cytosolic glutathione (17,(135)(136)(137)270), the redox milieu of pancreatic b-cells promotes the signal spreading from mitochondria up to the targets within the plasma membrane, which can further switch-on Ca V opening and action potential firing, followed by IGV exocytosis. It is unknown whether the redox signal spreading is enabled by a H 2 O 2 diffusion or by a redox relay, for example, via peroxiredoxins, thioredoxins, or glutaredoxins, abundant in pancreatic b-cells (97,204).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One cause of glucose toxicity is chronic oxidative stress [ 9 , 10 ]. Glucose produces reactive oxygen species (ROS) through oxidative phosphorylation, and when the ROS concentration exceeds the physiological range as a result of hyperglycemia, it can cause tissue damage including β cells, which are especially susceptible to oxidative stress due to poor intrinsic antioxidant defenses [ 11 ]. Specifically, when β cells are attacked by ROS, mitochondrial dysfunction occurs and signaling that normally links glucose metabolism and insulin secretion is disrupted [ 12 , 13 ].…”
Section: Regulation and Turnover Of Human β-Cellsmentioning
confidence: 99%